1996
DOI: 10.1152/ajprenal.1996.271.2.f292
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dependence of integrity of the actin cytoskeleton of proximal tubule cell microvilli

Abstract: To better define the role of Ca2+ in pathophysiological alterations of the proximal tubule microvillus actin cytoskeleton, we studied freshly isolated tubules in which intracellular free Ca2+ was equilibrated with highly buffered, precisely defined medium Ca2+ levels using a combination of the metabolic inhibitor, antimycin, and the ionophore, ionomycin, in the presence of glycine, to prevent lethal membrane damage and resulting nonspecific changes. Increases of Ca2+ to > or = 10 microM were sufficient to init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…morphological changes and membrane permeabilising activity) induced by diC14-amidine are related. The disturbance in membrane integrity may induce an elevation of the Ca 2+ level in the cytosol, which was shown by others to cause actin filament disassembly [27]. Observation of the morphology of the actin cytoskeleton (with TRITC-phalloidin) showed neither the changes related to the membrane morphology nor visible changes in actin filament density (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…morphological changes and membrane permeabilising activity) induced by diC14-amidine are related. The disturbance in membrane integrity may induce an elevation of the Ca 2+ level in the cytosol, which was shown by others to cause actin filament disassembly [27]. Observation of the morphology of the actin cytoskeleton (with TRITC-phalloidin) showed neither the changes related to the membrane morphology nor visible changes in actin filament density (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…[31][32][33] Without extra protective substrates during hypoxia or reoxygenation, the majority of tubules showed little or no recovery at the end of reoxygenation (Figure 3e). With addition of ␣KG/ASP during reoxygenation, most tubules recovered a normal appearance of F-actin and fodrin (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%
“…28,32,33 Tubules were suspended at 3.0 to 5.0 mg of tubule protein/ml in a 95% O 2 /5% CO 2 5.0 sodium butyrate, 3% dialyzed dextran (T-40, Pharmacia), and 2 glycine. Medium A was also supplemented with 0.5 mg/ml of bovine gelatin (75 bloom) to suppress aggregation of the isolated tubules during the prolonged experimental incubation periods.…”
Section: Isolation Of Tubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that ischemic changes lead to ATP depletion and cause cytoskeletal alterations. 31,32,[34][35][36] Thus, both a direct action of the venom and an indirect ischemic mechanism may induce morphologic and functional renal alterations. Ischemia has been associated with changes in arterial pressure and the deposition of fibrin thrombi in renal capillaries, neither of which was observed with B. moojeni venom.…”
Section: Discussionmentioning
confidence: 99%